Association between in-hospital antibiotic use and long-term outcomes in critically ill patients - Parker Burrows; Ruth-Ann Brown; Abigail Samuelsen; Anthony S. Bonavia (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract